Аntijudicial dictionary: reglamentation of language etiquette in laws - Нелюба, Анатолій Миколайович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The language of the contemporary Ukrainian law has surzhik and jargon characteristics; the terminology and nomenclature of law is not an exception. One of the methods of overcoming this state is the inventory checking and codification of law terminology. The task of this article is to make antijudicial dictionary fragments open to public as one of the possible ways of terminological inventory and codification. The examples of language etiquette addressing are given by way of illustration, which became the component part of judicial nomenclature at recent age – are entrenched by this or that law as law standards: товариш, ваша честь, шановний суд. The structure of the language entry has the following elements: the title of the article; the reference to the corresponding law or the statutory enactment, language or judicial analysis, the offered correct variant or variants.